Risk Perception as a Mediator in Explaining the Relationship of Cognitive Biases and New Venture Creation. (July 2022) - Riasudeen, S.; Ratnoo, Himmat Singh; Kannadhasan, M.; Singh, Pankaj
The study investigates the role of risk perception in mediating the association of certain important cognitive biases such as overconfidence, illusion of control, optimism and planning fallacy with new venture creation. The study collected responses through questionnaires from 375 entrepreneurs in Central India. Partial least squares path modelling has been used to gauge the way these variables are connected. This study finds only the illusions of control and optimism to have lowered the perceptions of risk, and this lowering has resulted in the creation of a new venture. However, contrary to past studies, overconfidence and planning fallacy are directly linked with the decision to start a new project. Careful assessment of the levels of risk perception may enable entrepreneurs to minimise the cognitive biases, and they can constructively get engaged in the performance of the venture.